Cartas de aconselhamento: espaço dialógico da socioconstrução da imagem de si - Farias-Marques, Maria do Socorro de Almeida (2009)
The aim of this work is analyze the rates of modalization in the discursive genre advice letter, in order to observe how they help in the construction of self image. We are interested in the analysis of images that the authors of letters build in their discourses. As second objective, we intend to verify if the discourses of the letters break with the traditional stereotype of female figure and its social role or pointed traditional roles. The corpus of that work is compound for six advice letters published in the column Consultório Sentimental of Veja.com Magazine and signed by the columnist Betty Milan. The analysis is made based in the rules of Bakhtin about the genres of discourse, the notion of ethos discoursed by Amossy (2005) and Maingueneau (2001, 2005, 2008) and of Kerbrat-Orecchioni (1980) about the rates of modalization. The studies of Bakhtin were used to analyze the advice letters while genre of discourse, considering theirs constituents (theme, style, and composition) and theirs authors. As the studies about media and social construction of genre, we intend to point the role of media in the spread of social roles of women and men in social relations. These are built in the interaction among women, men and society.